Noninvasive ventilation of a patient with acute respiratory insufficiency caused by COVID-19 pneumonia: Case report - Vulović Jelena; Knežević Snežana (ABC: časopis urgentne medicine, 2022)
Introduction: Since the beginning of the COVID-19 pandemic, the healthcare system has reorganized, created, and implemented protocols on triage, treatment, indications for hospitalization in intensive care units, and indications for non-invasive and mechanical ventilation. This case report aimed to demonstrate the successful treatment with noninvasive ventilation of a patient with acute respiratory failure in COVID19 pneumonia. Case Report: A 57-year-old patient with comorbidities was admitted to the COVID-19 intensive care unit due to weakness, dry cough, shortness of breath, and difficulty breathing. On admission, SpO2 64%, blood pressure 120/80 mmHg, frequency 160/min., respirations 25/min., temperature 38.6oC, with signs of acute respiratory insufficiency and laboratory-confirmed cytokine storm. Bilateral interstitial pneumonia was radiologically verified. He was treated according to the protocol for COVID-19, with non-invasive ventilation that was applied for 35 days, with constant supervision by an anesthesiologist. Complications, intubation, and mechanical ventilation were prevented. The patient was discharged to home treatment after 62 days in a stable general health condition. Conclusion: The role, knowledge, experience, and constant supervision of anesthesiologists in the intensive care unit during the coronavirus pandemic are significant. Successful treatment using noninvasive ventilation in the presented case contributed to a positive outcome of the disease.